2009
DOI: 10.1515/cclm.2009.249
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of test report delivery to the requesting physician in an outpatient setting: an observational study

Abstract: Background: Clinical laboratories accredited according to ISO 15189 quality standards are obliged to implement and continuously monitor quality indicators for evaluation of the laboratory's contribution to patient care. Reporting laboratory results to the requesting physician is one important phase of the clinical laboratory testing process. Failure to report results may indicate the ineffectiveness of the laboratory service. We aimed to analyze the proportion and type of laboratory reports for outpatients tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This unnecessary expense not only increases the workload of already overburdened laboratory staff but also prevents the introduction of newer and more sensitive/specific tests due to loss of a considerable amount of the laboratory budget on useless investigations. In a similar study it was reported that out of a total of 22445 laboratory tests, 464 test reports were not collected with 30% of the average monthly budget been wasted [7]. The physicians are in the habit of ordering a panel of tests for a particular condition with only one or two investigations out of them contributing towards clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This unnecessary expense not only increases the workload of already overburdened laboratory staff but also prevents the introduction of newer and more sensitive/specific tests due to loss of a considerable amount of the laboratory budget on useless investigations. In a similar study it was reported that out of a total of 22445 laboratory tests, 464 test reports were not collected with 30% of the average monthly budget been wasted [7]. The physicians are in the habit of ordering a panel of tests for a particular condition with only one or two investigations out of them contributing towards clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Total number of tests performed at AFIP and CMH Rawalpindi laboratory during the study period and number of uncollected reports were noted. Laboratory reports were considered uncollected if not collected either by hand, on the telephone or via the internet within 3 months after being issued [7]. Moreover, we interviewed the physicians and pathologists at CMH Rawalpindi, MH Rawalpindi and AFIP to get their point of view regarding incomplete laboratory request forms, inappropriate test requests at various professional levels and uncollected reports all the above mentioned issues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Young age is associated with reduced likelihood of returning for test results [14] and being more likely to have unstable living situations [15-18]. These associations will reduce the chances that a young individual will learn the results of HIV testing from providers or public health personnel.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] From the beginning to the end of the laboratory testing process, the generic monitors were QT17-outpatient order-entry error rates, 13,14 QT1-identification (ID) band defect rates, 15,16 QT3-specimen rejection rates, [17][18][19][20] QT15-median troponin order-to-report times, 21,22 QT8-STAT test receipt-to-report TAT outlier rates, 23,24 QT10-critical value reporting event-defect rates, 25,26 and QT16-corrected report rates. 27,28 …”
Section: Q-tracks Monitor Programmentioning
confidence: 99%